Faunistic and bibliographical inventory of moth flies from Ukraine (Diptera, Psychodidae) - Ježek, Jan; Chvojka, Pavel; Manko, Peter; Oboňa, Jozef (ZooKeys, 2017)
All important published records for 11 moth fly species known so far from Ukraine are reviewed (Phlebotominae 10 species, Psychodinae 1 species). Occurrences of two problematic taxa, Phlebotomus (Adlerius) brevis Theodor & Mesghali, 1964 and P. (Larroussius) major major Annandale, 1910, and some synonymies are discussed. Threticusnegrobovi Vaillant, 1972 must be deleted for Ukraine (misstatement). First records of 34 species of Psychodinae (tribes Mormiini, Paramormiini, Psychodini, Pericomaini) and one of Sycoracinae from Ukraine are also listed.
Keywords: Diptera; Phlebotominae; Psychodinae; Ukraine; faunistics; Psychodidae; Sycoracinae; first records